How innovative are spin-offs at later stages of development? Comparing innovativeness of established research spin-offs and otherwise created firms - Anna Lejpras (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The literature argues that research spin-offs (RSOs)-enterprises originating from a university or research institute-appear to have higher innovative potential and capabilities than other start-ups, at least in the early stages of their development. Yet, little is known about the innovative performance of these companies at later development phases. Thus, the main goal of this study is to investigate whether there are any differences in R&D and innovation behavior between established and/or mature RSOs and otherwise created firms and, if so, to what extent they are driven by networking and cooperation activities as suggested by some scholars. To this end, we employ probit regression analysis and a matching approach using survey data on more than 6,000 East German firms, among which are 179 RSOs. Our first findings suggest that established RSOs engage in R&D and innovation activities more frequently than companies whose genesis was of another type. Nevertheless, the results obtained when accounting for collaboration measures show that the precedence of RSOs in further development stages over otherwise created firms in terms of innovativeness is related to their higher intensity of cooperation activity and close, face-to-face interactions with universities, and not to type of firm creation. Moreover, our findings reveal that cooperating in various fields may be of different importance for specific inputs and outputs of the innovation activity. Finally, based on our results, we draw some implications both for practicing managers and public policymakers.
Keywords: M20; L20; O30; 330; Spin-Offs; R&D; Innovation; Cooperation